Challenges Faced by Part-Time Doctoral Students in Managing Psychological Well-being: A Qualitative Study - Rashid, Rahayu Ab; Rafie, Umi Nazira; Ramli, Nur Sakinah; Noor, Muhd Fariduddin Athar Mohd; Sharkawi, Sharizan (Advances in Social Sciences Research Journal, 2023)
The emergence of alarming statistics on Psychological Well Being (PWB) among doctoral students has received critical attention in the media and across the higher education sectors. Complex work in the doctoral journey has been perceived to be draining thus affecting students’ well-being which could lead to mental depression. Understanding relevant challenges in managing PWB could be a prime opportunity for intervention strategies in managing PWB among part-time doctoral students. This paper hopes to contribute to the dearth of studies of PWB on part-time doctoral students, particularly in Malaysia. A qualitative study would uncover detailed accounts and underlying issues on the challenges of managing PWB faced by part-time doctoral students in Malaysia. Purposive sampling and snowball sampling were used in this study. Five part-time doctoral students were selected and invited to participate in the semi-structured interview. The participants expressed their PWB by describing their experience in the doctoral journey. This study's findings concluded on two main themes involved in maintaining PWB; internal and external challenges. Personal occurrences represent the internal challenge, whereas the internal environment and academic process represent the sub-themes under external challenges. It is essential for doctoral students to focus on their personal occurrences especially maneuvering things that are within their control and dealing with external challenges in managing PWB during the doctoral journey.